2022
DOI: 10.1111/psyp.14114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of task load, spatial attention, and trait anxiety on neuronal responses to fearful and neutral faces

Abstract: Facial emotional expressions constitute a significant part of communication as they transfer non-verbal signals to others. Especially for expressions signaling threat or danger, distinct early and mid-latency event-related potentials (ERPs) modulations are reported (e.g., see Mühlberger et al., 2009;Schupp et al., 2004;Yoon et al., 2016), even if facial emotion remains task-irrelevant, suggesting high automaticity of emotion discrimination by specific ERP components Smith, 2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 104 publications
1
12
0
Order By: Relevance
“…Besides the N170, also the EPN was larger for fearful compared to neutral faces in accordance with various previous studies 27 , 44 , 59 , 87 , 88 , confirming that the EPN differentiates between fearful and neutral faces in a paradigm that does neither direct attention away from the stimuli 27 , nor requires attentional focus on the emotional expression 70 . Classification maps reveal that especially the left-hemispheric EPN is sensitive to facial features and that this sensitivity is restricted to low spatial frequencies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Besides the N170, also the EPN was larger for fearful compared to neutral faces in accordance with various previous studies 27 , 44 , 59 , 87 , 88 , confirming that the EPN differentiates between fearful and neutral faces in a paradigm that does neither direct attention away from the stimuli 27 , nor requires attentional focus on the emotional expression 70 . Classification maps reveal that especially the left-hemispheric EPN is sensitive to facial features and that this sensitivity is restricted to low spatial frequencies.…”
Section: Discussionsupporting
confidence: 90%
“…One important trait related to altered threat detection and perception is trait anxiety, which has been proposed to lead to hypervigilant processing of threat-related stimuli [19][20][21][22] . However, while early studies reported increased early ERPs for fearful faces in high trait-anxious participants [23][24][25] , other studies found no effect 26,27 or even attenuated differential ERPs 28,29 . Thus, although theoretical arguments (e.g., 21,23 ) strongly suggest a relation between trait anxiety and early neural responses to threat, findings are inconclusive.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…P1 amplitude modulations might reflect recurrent effects of the amygdala on activations in visual areas, which have been associated with the P1 across different methodological approaches (intracranial recordings, see Méndez-Bértolo et al, 2016; lesion studies, see Mielke et al, 2022; Rotshtein et al, 2010; combined EEG-fMRI measures, see Müller-Bardorff et al, 2018). Of note, given the notoriously lower reliability of P1 emotional modulations (Schindler & Bublatzky, 2020), several previous studies showed no significant P1 emotion effects for central (e.g., see Itier & Neath-Tavares, 2017; Neath-Tavares & Itier, 2016; Schindler, Richter, et al, 2022) and peripheral locations for fearful or angry faces (Rigoulot et al, 2012; Schindler, Busch, et al, 2022) or peripheral simple negative pictures (Carretié et al, 2017, 2020). This discrepancy might be explained by specific features of our study, including the relatively large EEG sample, the sustained attention to peripheral locations, and the use of monetary reward.…”
Section: Discussionmentioning
confidence: 88%